Képzési franchise rendszer kialakítása a TÜV Rheinland Intercert Kft-nél - Geresdi Krisztina (2015)
The topic of my thesis is to develop a franchise system on training. There are numerous franchise systems we can meet day by day and can buy at the partners. The franchise model, the business practice and the image are unified. There are some examples among educational companies, mainly language schools, operating in franchise system. Although it would be unique in Hungary that a company providing training and certification tried to develop a franchise system. I wanted to find it whether it would be worth introducing a franchise system at the company. If we want to develop a franchise system what sort of products or services would be worth including? How would it influence the present operational practice of the company and the variety of training programmes? Would it be possible to develop a complex system besides the training programmes? I tried to find the answers to these questions in my thesis. In the first part of my thesis I introduce the advantages, disadvantages and elements of franchise systems. After that, I investigate how to introduce a franchise system step by step for the case the management of the company decides to franchise. In order to make a responsible decision on franchise, the present operational practice has to be examined. What are the strong and weak points of the company that needs improvement? What sort of advantages and risks would accompany the development and introduction of the model? I introduce the detailed investigation of the present situation with PEST, SWOT and Porter analysis. The detailed investigations can be found in the second part of my thesis. After examining the elements of franchise systems and the present situation of the company on the training market we can determine the elements of the prospective franchise model. In the third part the development of the franchise system can be found. We determine what has to be provided by the Franchisor and what kind of requirements has to be met by the Franchisee. After that I introduce the elements of the franchise system covering the: • use of the logo of TÜV Rheinland Interc Kft • certification of the trainers • certification of the training programmes The final objective of the thesis is to provide an overall analysis and develop a franchise system introducing the current operation of the company. In addition to the introduction of the elements of the franchise system, providing a complex information system for the top management of the company that is entitled to make a decision to franchise.